Super-High Magnification Dermoscopy in 190 Clinically Atypical Pigmented Lesions - Cinotti, Elisa; Cioppa, Vittoria; Tognetti, Linda; Perrot, Jean Luc; Rossi, Renato; Gnone, Matteo; Cartocci, Alessandra; Rubegni, Pietro; Cortonesi, Giulio (Diagnostics (Basel), 2023)
Super-high (×400) magnification dermoscopy (D400) is a new non-invasive imaging technique that has been shown to add information for the differential diagnosis of melanocytic lesions in a pilot study. Our study aimed to confirm if D400 can add details for the discrimination of clinically atypical nevus and melanoma. This is a retrospective observational, multicentric study enrolling patients who received ×20 (D20) and ×400 (D400) magnification dermoscopic examinations of pigmented skin lesions. Dermoscopic images were retrospectively evaluated by three observers for the presence/absence of nine D20 and twenty D400 dermoscopic features defined in the previous pilot study. Univariate and multivariate analyses were carried out to find predictors of benign and malignant behaviors. At D20, an atypical pigment network, blue-whitish veil, atypical vascular pattern, regression, and homogenous pattern were more frequent in melanoma than in nevi (p < 0.001). At D400, melanoma showed more frequently than benign lesions, melanocytes with an irregular arrangement and irregular in shape and size (p < 0.001). A network with edged papillae was more frequent in benign lesions than melanomas (p < 0.001). Our study confirms that D400 can identify melanocytes with an irregular arrangement, and irregularities in shape and size in melanomas, adding information to the conventional D20 examination.